Nitazoxanide superiority to placebo to treat moderate COVID-19 – A Pilot prove of concept randomized double-blind clinical trial. (July 2021) - Blum, Vinicius Fontanesi; Cimerman, Sérgio; Hunter, James R; Tierno, Paulo; Lacerda, Acioly; Soeiro, Alexandre; Cardoso, Florentino; Bellei, Nancy Cristina; Maricato, Juliana; Mantovani, Nathalia; Vassao, Marcella; Dias, Danilo; et al.
Abstract: Background: The absence of specific antivirals to treat COVID-19 leads to the repositioning of candidates' drugs. Nitazoxanide (NTZ) has a broad antiviral effect. Methods: This was a randomized, double-blind pilot clinical trial comparing NTZ 600 mg BID versus Placebo for seven days among 50 individuals (25 each arm) with SARS-COV-2 RT-PCR+ (PCR) that were hospitalized with mild respiratory insufficiency from May 20 th, 2020, to September 21 st, 2020 (ClinicalTrials.gov NCT04348409). Clinical and virologic endpoints and inflammatory biomarkers were evaluated. A five-point scale for disease severity (SSD) was used. Findings: Two patients died in the NTZ arm compared to 6 in the placebo arm ( p = 0.564). NTZ was superior to placebo when considering SSD ( p < 0001), the mean time for hospital discharge (6.6 vs. 14 days, p = 0.021), and negative PCR at day 21 ( p = 0.035), whereas the placebo group presented more adverse events ( p = 0.04). Among adverse events likely related to the study drug, 14 were detected in the NTZ group and 22 in placebo ( p = 0.24). Among the 30 adverse events unlikely related, 21 occurred in the placebo group ( p = 0.04). A decrease from baseline was higher in the NTZ group for d -Dimer ( p = 0.001), US-RCP ( p < 0.002), TNF ( p < 0.038), IL-6 ( p < 0.001), IL-8 ( p = 0.014), HLA DR. on CD4 + T lymphocytes ( p < 0.05), CD38 in CD4 + and CD8 + T (both p < 0.05), and CD38 and HLA-DR. on CD4+ ( p < 0.01) Interpretation: Compared to placebo in clinical and virologic outcomes and improvement of inflammatory outcomes, the superiority of NTZ warrants further investigation of this drug for moderate COVID-19 in larger clinical trials. A higher incidence of adverse events in the placebo arm might be attributed to COVID-19 related symptoms.